Antagonistic and Detoxification Potentials of Trichoderma Isolates for Control of Zearalenone (ZEN) Producing Fusarium graminearum - Tian, Ye; Tan, Yanglan; Yan, Zheng; Liao, Yucai; Chen, Jie; De Boevre, Marthe; De Saeger, Sarah; Wu, Aibo (Frontiers in Microbiology, 2018)
Fungi belonging to Fusarium genera can infect crops in the field and cause subsequent mycotoxin contamination, which leads to yield and quality losses of agricultural commodities. The mycotoxin zearalenone (ZEN) produced by several Fusarium species (such as F. graminearum and F. culmorum) is a commonly-detected contaminant in foodstuffs, posing a tremendous risk to food safety. Thus, different strategies have been studied to manage toxigenic pathogens and mycotoxin contamination. In recent years, biological control of toxigenic fungi is emerging as an environment-friendly strategy, while Trichoderma is a fungal genus with great antagonistic potentials for controlling mycotoxin producing pathogens. The primary objective of this study was to explore the potentials of selected Trichoderma isolates on ZEN-producing F. graminearum, and the second aim was to investigate the metabolic activity of different Trichoderma isolates on ZEN. Three tested Trichoderma isolates were proved to be potential candidates for control of ZEN-producing producers. In addition, we reported the capacity of Trichoderma to convert ZEN into its reduced and sulfated forms for the first time, and provided evidences that the tested Trichoderma could not detoxify ZEN via glycosylation. This provides more insight in the interaction between ZEN-producing fungi and Trichoderma isolates.